A retrospective analysis of 3 156 admissions with fever of unknown origin in a large Italian hospital (Epidemiology, Biostatistics, and Public Health, 2022)
Background: fever of unknown origin (FUO) is defined as a fever with no etiologic diagnosis after standardized investigations performed during 3 days in hospital or after at least 3 ambulatory visits. Our study aims to describe the epidemiology of classic FUO through the retrospective analysis of 902 861 admissions to a large University Hospital in Italy, to investigate its temporal trend, and to evaluate differences between young and old patients.Methods: we retrieved data records of all the admissions between the 1st January 1988 and 31st December 2007. Proportional admission rate (PAR ) of FUO was calculated. Time trends of FUO admissions were analysed by joinpoint regression, with time changes expressed as Expected Annual Percent Change (EA PC). The ICD 9-CM code was used to identify the diagnosis on discharge of FUO cases.Results: in the study period 3 156 patients were admitted with a diagnosis of FUO (PAR=3.50 per 1 000). The time-trend analysis showed two joinpoints, the first in 1995 (EAPC of 307.80, 95% CI: 89.66-776.84, p=0.002), and the second in 1998 (EAPC=-8.57, 95% CI: -10.37-6.73; p